'Talking about mobility': Garos aspiring migration and mobility in an 'insecure' Bangladesh. Issue 4 (1st October 2016) - Raitapuro, Minna; Bal, Ellen
ABSTRACT: All around the world, people are exposed to information and imageries that may have been generated in far-away places, but by implication become part of their everyday lives. These cultural imaginaries, whether 'realistic' or not, are widespread and have real-life consequences. They do not only produce new self-images, aspirations and ideals, but also transform notions of (aspired) belonging and mobility. In this article, we show how mobility (transnational connectivity, spatial, social and economic mobility) plays an important role in the everyday life and future aspirations of young members of the indigenous community of Garos in Bangladesh. In the contemporary globalizing context of Bangladesh, young Garos have constructed aspirations which can no longer be fulfilled in their native villages. With this case study of social and cultural meanings of mobility for indigenous youth, we also wish to contribute to a better understanding of past and present processes of social transformation amongst indigenous peoples in Bangladesh. While previous studies of indigenous minorities in South Asia are characterized by a focus on stillness and stasis rather than change and mobility, this article calls for a differing approach in ethnographic research on ethnic minorities, one which recognizes the mobile and (globally) connected context and challenges dominant notions of 'tribal' or 'indigenous' communities as frozen in time and space.